Comparison of the outcome of orthodontic dental movement using aligners versus fixed orthodontics: A review - Malpartida-Pacheco, Mónica Ivette (2023)
Introduction: The aligners have become a preferred alternative in terms of orthodontic treatment, surpassing the choice of conventional brackets, due to the comfort and aesthetics that the aligners represent, however, the final result with this system continues to be a controversial issue. The objective of this review was to verify the effectiveness of the treatment completed with aligners versus conventional brackets. Materials and methods: An exhaustive search was carried out in the PubMed, ScienceDirect, Scopus and Embase databases up to the date of January 5, 2023, including comparative studies that evaluated the final result and treatment time of the aligners compared to conventional braces. Two researchers carefully selected the articles evaluated and analyzed different key topics on the subject. Results: In this study, 8 articles were included, according to the studies, the vast majority did not find significant differences in completion between the compared groups. In addition to this, the treatment time in 3 articles was faster with aligners, in 3 articles it was faster with conventional brackets, and in one article no significant difference was found, so it is not yet established whether a system is faster than the other. Conclusions: Both aligners and conventional fixed orthodontics had good results at the end of orthodontic treatment and presented a similar treatment time, however, the majority of treated cases belonged to malocclusions of medium to low complexity, so these cannot be generalized. findings to all malocclusions.